CLASSIFICATION OF INDIVIDUAL LABOR DISPUTES - Rahimqulova Lola (Scholar Express Journals, 2022)
This article presents a scientific analysis of the causes of individual labor disputes in the National Labor Relations of the Republic of Uzbekistan. Factors provoking labor disputes also fall under the scope of the International Labor Organization. The labor disputes that are taking place in the country today and their classification have been studied with the help of the opinions of scientists
Keywords: Labour; International Labour organization; Uzbekistan; code